Statistics for behavioral sciences Fred Fallik, Bruce Brown ; advisory editors, Wendell E. Jeffrey, Salvatore R. Maddi, Bruce Ekstrand - FALLIK, Fred; Brown, Bruce; Jeffrey, Wendell E; Maddi, Salvatore R; Ekstrand, Bruce (1983)
xxxiii, 538 hlm ilus 28 cm